ROLE AND RESPONSIBILITY OF A UNIVERSITY IN MILITARY AND PEACE RESEARCH - Maclachlan, Gordon; Bell, Gordon G.; Fulton, E. Margaret (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1987)
The image of the university community blindly carrying out research for government agencies or industry is not an unfamiliar one. It is important for society to know whether or not the image reflects a reality or is a fabrication of those interested in undermining the universities. Gordon Maclachlan engages the issue by clearly stating the policies and structures that one university - McGill - has in place to meet the complex nature of the question. George Bell insists that the question be asked in a broader context than that of a university's image of itself and its sense of total academic freedom. The university is an integral part of the community that supports it, and has its role in helping to keep that community secure. E. Margaret Fulton calls for a significant shift in the policies generally held in universities away from any research that could he considered "tainted", and toward research in the interests of peace. RÉSUMÉ L'image d'universités conduisant aveuglément des recherches pour le compte d'organismes d'Etat ou d'entreprises industrielles a quelque chose de familier. Il est important que la société sache si oui ou non cette image reflète la réalité ou si c'est une pure invention de ceux qui cherchent à saper la crédibilité des universités. Gordon Maclachlan aborde le problème en exposant clairement les politiques et les structures mises en place par une université - en l'occurrence McGill - pour faire face à la nature éminemment complexe de cette question. George Bell insiste pour que la question soit posée dans un contexte plus large que celui de l'image d'une université et de son sens de liberté académique intégrale. L'université fait partie intégrante de la communauté qui assure son soutien et elle a son rôle à jouer pour garantir la sécurité de cette communauté. E. Margaret Fulton préconise une désaffection à l'égard des recherches qui risquent de passer pour "entachées" en faveur de recherches menées dans l'intérêt de la paix.